Comparison of water turnover rates in young swimmers in training and age-matched non-training individuals - Leiper, J. B.; Maughan, R. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
Total body water (TBW) and water turnover rates (WTR) of 8 competitive swimmers (SW) and 6 age-matched non-training individuals (CON) were determined using deuterium oxide dilution and elimination. During the 7-day study, individuals in the SW group trained 9 times, swimming on average 42.4 km, while the CON group did no regular exercise. Water temperature in the swimming pool was between 26 and 29 °C during training sessions. Body mass at the beginning and end of the study period remained essentially the same in the SW (67.8 ± 6.3 kg) and CON (61.1 ± 8.5 kg) groups. Mean ± SD TBW of the SW (38.7 ± 5.6 L) was similar to that of the CON (37.5 ± 8.0 L). Mean WTR was faster in the SW (54 ± 18 ml · kg · day-1) than the CON (28 ± 21 ml · kg· day-1). Mean daily urine output was similar in the SW (14 ± 5 ml · kg · day-1) and CON (14 ± 3 ml · kg · day-1). Calculated non-renal daily water loss was faster in the SW (41 ± 21 ml · kg · day-1) than the CON (13 ± 20 ml · kg · day-1). This study demonstrates that WTR are faster in young swimmers who exercise strenuously in cool water than in non-training individuals and that the difference was due to the approximately 3-times greater non-renal water losses that the exercising group incurred. This suggests that exercise-induced increases in sweat rates are a major factor in water loss in swimmers training in cool water.